Randomised controlled trials in educational research: Ontological and epistemological limitations - Michael Rowe; Carmen Oltmann (South African Medical Association, 2016)
Randomised controlled trials (RCTs) are a valued research method in evidence-based practice in medical and clinical settings because they are associated with a particular ontological and epistemological perspective that is situated within a positivist world view. It assumes that environments and variables can be controlled to establish cause-effect relationships. However, current theories of learning suggest that knowledge is socially constructed, and that learning occurs in open systems that cannot be controlled and manipulated as would be required in a RCT. They recognise the importance and influence of context on learning, which positivist research paradigms specifically aim to counter. We argue that RCTs are inappropriate in education research because they force one to take up ontological and epistemological positions in a technical rationalist framework, which is at odds with current learning theory.